Development Analysis of Public Electric Vehicle Charging Station in Indonesia Using Ecosystem Pie Model and Triple Layered Business Model Canvas - Fredicia Angelia Kezia Boanito Sirait; Joko Siswanto (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
Accelerating the adoption of electric vehicles is a crucial strategy for Indonesia to achieve its 2060 Net Zero Emission goal. One of the driving factors behind this transition is the development of Public Electric Vehicle Charging Stations (PEVCS). However, the existing PEVCS infrastructure in Indonesia does not yet fully prioritize interoperability and sustainability. This research presents the results of a literature review and field study aimed at developing an integrated and sustainable PEVCS business model, using the Ecosystem Pie Model and the Triple Layered Business Model Canvas. This study adopts a qualitative case study approach involving three PEVCS ecosystem entities in Indonesia. The findings of this study represented the first stage in developing an integrated and sustainable PEVCS business model, providing insights into the roles of entities and value creation mechanisms within the ecosystem